Pengaruh Total Quality Service dan Sistem Pengendalian Internal terhadap Kinerja Organisasi Dimediasi oleh Layanan Digital - Ika Santi; Titik Kusmantini; Hendro Widjanarko (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Improving the quality of healthcare services became a major challenge for healthcare facilities to remain competitive and meet patient expectations. Total Quality Service (TQS) and Internal Control Systems were key factors in enhancing organizational performance, supported by the increasingly developed digital services. This study aimed to analyze the effect of Total Quality Service (TQS) and Internal Control Systems on Organizational Performance, mediated by Digital Services, in healthcare facilities in Bantul Regency. This research used a quantitative method. Data were collected through questionnaires distributed to managers and owners of healthcare facilities in Bantul Regency. The data analysis technique used Structural Equation Modeling (SEM) with SmartPLS analysis tools. The results showed that Total Quality Service and Internal Control Systems had a significant effect on Organizational Performance. Furthermore, Digital Services mediated the relationship between Total Quality Service and Organizational Performance, as well as the relationship between Internal Control Systems and Organizational Performance. This indicated that the optimal implementation of digital services could enhance the effectiveness of quality management and internal control systems in improving the performance of healthcare facilities